Management of a Congenital Flexural Deformity in a Calf - Surgical and Pathological Aspects - Fernandes, Maria Eduarda dos Santos Lopes; Carvalho, Luiza de Albuquerque; Chenard, Marina Galindo; Pitombo, Cícero Araújo; dos Santos, Orlei Justen; Caldas, Saulo Andrade; Nogueira, Vivian de Assunção; Helayel, Michel Abdalla (Acta Scientiae Veterinariae, 2020)
Background: Flexural deformities are anatomical deviations, in varying degrees, of one or more joints, and may have a congenital or acquired origin. Congenital contracture of the deep digital flexor tendon (DDFT) affects newborn calves and results in hyperflexion of the metacarpal-phalangeal joint, which in severe cases means that the animal must support its own weight on its fetlock joints. The aim of this study is to report the rapid and successful result of applying bilateral total tenotomy technique on a newborn bovine that had been diagnosed with severe bilateral DDFT contracture in the thoracic limbs. Case: A 3-week-old male bovine with a history of difficulty in maintaining a quadrupedal position was attended at the Veterinary Hospital of the Federal University of Tocantins. The animal had severe bilateral locomotor alterations in the thoracic members to the point that he walked on his fetlock joints. The physical examination revealed clinical parameters within the normal range. However, the locomotor system examination showed severe flexor deformity in the bilateral metacarpal-phalangeal joints, and the limbs were being supported on the dorsal face of the fetlock joints, which presented ulcerations, and was suggestive of a shortening of the DDFT. Based on the patient’s history and clinical examination, as well as the severity of the tendon contractures, surgical treatment using the DDFT bilateral total tenotomy technique was decided upon. Postoperative treatment consisted of 2.5 mg/kg of enrofloxacin intramuscularly (IM), SID, for 5 days and 0.5 mg/kg meloxicam via IM, SID, for 3 days; as well as a dressing (cotton, medical bandage and a PVC mold) on the thoracic limbs to provide support and allow the animal to walk, until its complete recovery. One day after the surgery, the animal was able to walk with difficulty and some trembling; however, on the third day after the surgical procedure, it could stand up by itself, walk and graze normally. The surgical stitches were removed seven days after the operation, as the surgical wounds had healed adequately. The animal was followed-up for a one-month period after the total tenotomy, with no recurrence of any of the clinical signs, and the thoracic limbs had regained normal biomechanics. Discussion: Congenital flexural deformities are common in newborn calves of different breeds and their incidence is mainly in the thoracic limbs, especially in the carpal, distal interphalangeal and metacarpal-phalangeal joints as was reported in the animal in this study. The history and anamnesis of the animal, along with a thorough physical examination, in order to rule out any other congenital alterations, was extremely important in the diagnosis, and the classification of the severity of the deformity along with the choice of appropriate treatment in the present study. Although total tenotomy is rarely reported in the literature, and there are controversial results with calves, the surgical treatment was chosen in the present case due to the severity of the case. The DDFT bilateral total tenotomy surgical technique gave satisfactory results for the correction of severe bilateral flexor deformity in the thoracic limbs of the newborn crossbred calf. Complete recovery of the limb biomechanics was rapid, and there was no post-surgical complications, thus ensuring the animal could have a good and healthy life. Total DDFT tenotomy is considered a viable surgical procedure for calves with severe congenital flexor deformities; however, post-operative care is also important to ensure good final results.